석면해체 참여업체가 작업장 인근 주민 안전에 미치는 영향에 관한 연구 - 염희상; 박종용; 이덕희; Youm, Hie Sang; Park, Jong Young; Lee, Duck Hee (한국재난정보학회 논문집, 17(3), 2021)
Purpose: The purpose of this study is to analyze how the participating companies related to asbestos dismantling affect the safety of residents near asbestos dismantling worksites, and to present important criteria for selecting asbestos dismantling related companies based on the analysis results. Method: In this study, based on the Occupational Safety and Health Act and the Asbestos Safety Management Act, important items about participating companies related to asbestos dismantling and the safety of residents near the asbestos dismantling workshop were derived, and then questionnaire items were determined through FGI. Multiple regression analysis was performed to analyze the influence relationship. Result: In order to secure the safety around the asbestos dismantling site, it was confirmed that the ability of asbestos dismantling supervisors among the participating companies (dismantling companies, investigation agencies, and supervisors) had the greatest influence. Conclusion: It showed that it is essential to select an excellent asbestos dismantling supervisor and an excellent asbestos dismantling and removal company in order to ensure the safety of residents near the asbestos dismantling site. 연구목적: 석면해체 참여업체가 작업장 인근 주민 안전에 어떠한 영향을 미치는지 분석하고, 분석결과를 바탕으로 석면해체 참여업체의 선정에 있어서 중요 기준을 제시하는 데 목적이 있다. 연구방법: 본 연구에서는 산업안전보건법과 석면안전관리법을 토대로 석면해체 관련 참여업체와 석면해체 작업장 인근 주민 안전에 관한 중요항목을 도출한 후 FGI를 통하여 설문항목을 결정하였고, 영향관계 분석을 위해 다중회귀분석을 실시하였다. 연구결과: 안전한 석면해체 작업장 주변을 조성하기 위해서는 석면해체 관련 참여업체(석면해체·제거업자, 석면조사기관, 석면해체작업감리인) 중 석면해체작업감리인의 역량이 영향관계가 가장 큰 것으로 확인되었다. 결론:석면해체 작업장 인근 주민의 안전을 확보하기 위해서는 우수한 석면해체작업감리인과 우수한 석면해체·제거업자의 선정이 필수적임을 보여 주었다.